Semirational Design of SenC to Enhance Organic Selenium Biosynthesis - Kailin Shao; Xiaobin Yu; Yan Zhao; Ying Zhang; Xiaobo Liu (Microbial Biotechnology)
ABSTRACT Organic selenium, a bioavailable form of the essential trace element selenium, holds significant potential for improving human health through dietary supplements and functional foods. However, low bioconversion efficiency has primarily limited the biosynthesis of organic selenium compounds. Here, we focused on enhancing the biosynthesis of organic selenium by optimising the expression and activity of two key enzymes, SenB and SenC, involved in the conversion process. We compared several expression systems, including fusion expression and dual‐promoter approaches, and optimised reaction conditions such as temperature, pH and incubation time. Our results showed that mutations of SenC more than doubled enzyme activity, resulting in a corresponding rise in the intermediate SeP. Notably, the fusion expression of SenB and SenC exhibited the highest conversion rate of organic selenium, achieving over 95% under optimal conditions. Our findings provide a basis for organic selenium production through microbial biotechnology.